Understanding the Effect of Review Credibility, Perceived Usefulness, and Perceived Ease of Use towards Purchase Intention (A Study on K-Beauty Products in Shopee) - Afifah, Nadzima (Jurnal Ilmiah Mahasiswa FEB, 2021)
The rapid progress in digital technology makes online shopping even easier, moreover during pandemic COVID-19. In 2020, new e-commerce users estimated that there are around 12 million and Shopee was placed as the most visited e-commerce site in Indonesia by the fourth quarter in 2020. This study is aimed to analyze the influence of review credibility, perceived usefulness and perceived ease of use towards consumer purchase intention on K-Beauty product on Shopee. This study examine four variables such as Review Credibility (X1), Perceived Usefulness (X2), Perceived Ease of Use (X3) and Purchase Intention (Y). This study is descriptive research by using quantitative approach. The population in this study is Shopee’s customers. The sampling technique is purposive sampling in which some criteria is needed. The sample size is 161 respondent. Statistical software Smart-PLS is used to analyze the data in this study. This study shows review credibility, perceived usefulness, and perceived ease of use has a positive and significant effect on purchase intention.Keywords: Review Credibility, Perceived Usefulness, Perceived Ease of Use, Purchase Intention.